Research on the compressive strength properties of expanded perlite concrete under alternating temperatures - Yu, Pei; Xu, Kunkun (Archives of Civil Engineering, 2026)
In order to study the compressive strength performance of expanded perlite concrete under low-temperature alternating action, different mixing ratios, mesh sizes, and temperatures were selected as research parameters in this paper using 90–120 mesh, in vitro incorporation at 0%, 10%, 20%, 30%, and 40%. The external mixing ratio of 30% was used, with mesh sizes of 30–50, 50–70, 70–90, and 90–120 mesh. The low-temperature alternating temperature was –20◦C and 20◦C, and 16 groups of 48 test blocks were designed and manufactured. Concrete compressive strength tests and SEM interface scanning tests were conducted. The results showed that the compressive strength of expanded perlite concrete with 90–120 mesh external addition was higher than that of ordinary concrete, and showed a trend of first increasing and then decreasing with the increase of external rate. When the external ratio was 30%, the compressive strength value was the highest, the compressive strength value increases with the increase of expanded perlite mesh size. Under low-temperature alternating action, the compressive strength values of expanded perlite concrete decrease. When using 90–120 mesh, the compressive strength loss rate gradually decreases with the increase of external mixing rate. When the external mixing ratio was 30%, the compressive strength loss rate was 9.16%, but still higher than that of ordinary concrete. Combining SEM to scan the concrete interface, the failure mechanism of the internal structure of expanded perlite concrete was explained from a microscopic perspective, confirming the rationality of the experimental data. According to the actual test results, it is proposed that using expanded perlite concrete with a 90–120 mesh addition ratio of 30% can effectively improve its compressive and frost resistance properties.